ArPNO-catalyzed acylative kinetic resolution of tertiary alcohols: access to 3-hydroxy-3-substituted oxindoles. Issue 32 (27th July 2022) - Yang, Min; Gao, Yu-Lin; Xie, Ming-Sheng; Guo, Hai-Ming
Abstract : Bifunctional chiral 4-aryl-pyridine- N -oxides were reported for the highly efficient acylative kinetic resolution of 3-hydroxy-3-substituted oxindoles with s -factor up to 167. Abstract : Bifunctional chiral 4-aryl-pyridine- N -oxides (ArPNO) were reported for the acylative kinetic resolution of 3-hydroxy-3-substituted oxindoles, where the oxygen acts as the nucleophilic site. Using less sterically hindered acetic anhydride, both the recovered tertiary heterocyclic alcohols and the ester products exhibited good to excellent results with s -factors up to 167. Control experiments supported the dual activation manner, where the N -oxide group and N–H proton in ArPNO were crucial for high selectivity and enhanced catalytic reactivity. Compared with the extensively used chiral NHC, isochalcogenourea, and DMAP catalysts, we found that chiral ArPNO were also efficient organocatalysts in the kinetic resolution of tertiary alcohols.